An area-wide real-time database for the euro area - Domenico Giannone; Jérôme Henry; Magdalena Lalik; Michele Modugno (European Central Bank (ECB), 2010)
This paper describes how we constructed a real-time database for the euro area covering more than 200 series regularly published in the European Central Bank Monthly Bulletin, as made available ahead of publication to the Governing Council members before their first meeting of the month. We describe the database in details and study the properties of the euro area real-time data flow and data revisions, also providing comparisons with the United States and Japan. We finally illustrate how such revisions can contribute to the uncertainty surrounding key macroeconomic ratios and the NAIRU.
Keywords: C01; C82; E24; E58; 330; database; euro area; real-time; revisions; Geldpolitik; Zeit; Datenbank; Natürliche Arbeitslosenquote; EWR-Staaten; USA; Japan